Neodymium isotopes in modern human dental enamel: An exploratory dataset for human provenancing - Plomp, E. (author) (Data in Brief, 2021)
This collection presents data on neodymium isotopes from modern dental elements (third molars) of 47 individuals born and raised in the Netherlands, Grenada, Curaçao, Bonaire, Columbia and Iceland. Neodymium isotope composition was successfully analyzed for 40 individuals (ranging between 0.511820 and 0.512773 143 Nd/ 144 Nd and -16.0 to 2.6 εNd), with neodymium concentration data available for 23 individuals (ranging between 0.1 and 21.0 ppb). For 37 individuals the dental elements have also been analyzed for strontium isotopes. All analyses were performed on a Thermo Scientific Triton Plus TIMS. Neodymium analyses were performed using 10 13 Ω resistors, with samples reanalyzed using 10 11 Ω resistors if enough sample was available. Strontium analyses were performed using 10 11 Ω resistors. A discussion about the applicability of the analysis technique and the results can be found in the article “Evaluation of neodymium isotope analysis of human dental enamel as a provenance indicator using 10 13 Ω amplifiers (TIMS)”. This dataset is available for verification of the provenance capability of neodymium isotope analysis in archaeological and forensic mobility studies. To ensure the interoperability and reusability of the data, the data is available on the IsoArcH (https://isoarch.eu/) data repository. Management Support